Endogenous Nitric Oxide Acts as a Natural Antithrombotic Agent In Vivo by Inhibiting Platelet Aggregation in the Pulmonary Vasculature - Emerson, Michael; Momi, Stefania; Paul, William; Francesco, Paolo Alberti; Page, Clive; Gresele, Paolo (Thrombosis and Haemostasis, 1999)
Nitric oxide (NO) is a powerful vasodilator and an inhibitor of platelet aggregation in vitro. While the ability of NO to modulate vascular tone in vivo has been proven, only a few studies have assessed its platelet inhibitory activity in vivo.We have employed two complementary animal models of pulmonary platelet thromboembolism to assess the antithrombotic activity of endogenous NO in vivo. The inhibition of nitric oxide synthase (NOS) by L-NAME significantly potentiated while the administration of the NOS substrate L-arginine significantly reduced the accumulation of 111In-labelled platelets in the pulmonary vasculature of rabbits induced by intravenous collagen plus epinephrine. L-NAME or L-arginine did not, however, modify 111In-labelled erythrocyte distribution in lungs and phenylephrine had no effect on platelet accumulation following collagen + adrenaline, suggesting that the effects of L-NAME were not due to vasoconstriction but rather to a direct modification of platelet function. In mice, L-NAME significantly reduced the dose of collagen + adrenaline required to induce thromboembolic mortality, increased the fall in circulating platelets and increased the % of pulmonary vessels occluded by platelet thrombi. The effects of L-NAME were reversed by L-arginine but not by a dose of nicardipine exerting maximal vasodilatation. Phenylephrine did not potentiate collagen + adrenaline-induced mortality.In the pulmonary vasculature in vivo, endogenous NO inhibits collagen + adrenaline-induced aggregation and enhances platelet disaggregation. This natural modulator function of NO is exerted via a direct effect on platelets and not as a result of haemodynamic changes.